Characteristics of the livestock market in Payobasuang, Payakumbuh - Reswati; Aronal Arief Putra (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
The livestock market in Payobasuang is an important animal market in the middle area of West Sumatra, mostly for cattle and buffalo trading. Research about the characteristics of this livestock market was conducted using a survey method. Data on trader demographics and livestock trading were collected from 30 traders. In demographics, all traders are men with an average age of 46.10 years old and 26.13 years of experience; 73.33% of them select this business as their primary occupation, and most of them have a vehicle to bring the animal (86.67%). Most traders' last education was elementary school (33.33%) and junior high school (33.33%). In livestock trading, most animals were obtained from livestock farmers (86.67%), and cash payments were mainly used (76.67%). For qurban and cattle racing, the female animal was preferred (65.93% and 100%, respectively), while the male was favored for the fattening animal (66.67%). In summary, the livestock market and traders are important in supplying livestock from smallholders to consumers.